1994
DOI: 10.1152/jappl.1994.77.1.357
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of oral cavity and laryngeal movements during swallowing

Abstract: In this study, dynamic imaging was used to track the movements of oral cavity and laryngeal structures during swallowing in 10 normal adults subjects. The movements of tiny lead pellet markers attached to the lips, tongue, mandible, and soft palate, as well as anatomic landmarks on the hyoid bone, were measured in relation to a reference pellet affixed to the upper central incisors. Sagittal views of the oral cavity were obtained using standard videofluorography. Each subject produced 10 swallows of 12 ml of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 7 publications
2
35
0
Order By: Relevance
“…22 Furthermore, this movement is affected by the insertion of an oral appliance [5][6][7] and expansion of the maxillary dental arch. 8 Hence, we speculated that deglutitive tongue movement would change to adapt to the new oral and maxillofacial morphology after orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Furthermore, this movement is affected by the insertion of an oral appliance [5][6][7] and expansion of the maxillary dental arch. 8 Hence, we speculated that deglutitive tongue movement would change to adapt to the new oral and maxillofacial morphology after orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Because deglutitive tongue movement was highly variable among different individuals, 6 the data recorded three times in each subject were averaged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the upward displacement was related to oral cavity events and the forward displacement to pharyngeal processes. Gay et al [14] evaluated swallowing function with and without bite blocks placed between the molars. With the bite blocks in place the tongue movement pattern differed between male and female subjects.…”
mentioning
confidence: 99%
“…any research studies have explored the sequence of the events of swallowing and have revealed that there is considerable variability between and within healthy individuals (Cook et al, 1989;Gay, Rendell, Spiro, Mosier, & Lurie, 1994;Kendall, 2002;Kendall, Leonard, & McKenzie, 2003;Kendall, McKenzie, Leonard, Gonçalves, & Walker, 2000;Logemann et al, 2000;Logemann, Pauloski, Rademaker, & Kahrilas, 2002;McConnel, Cerenko, Jackson, & Guffin, Jr., 1988;Mendell & Logemann, 2007;Ohmae, Logemann, Kaiser, Hanson, & Kahrilas, 1995). Factors contributing to this variability include bolus volume, bolus consistency, age, and gender (Cook et al, 1989;Kendall, 2002;Kendall et al, 2003;Logemann et al, 2000Logemann et al, , 2002Mendell & Logemann, 2007;Ohmae et al, 1995).…”
mentioning
confidence: 99%